Childhood Stroke: Long-Term Outcomes and Health-Related Quality of Life with a Special Focus on the Development of Epilepsy - von Stülpnagel, C.; Kutschker, Sebastian; Sperl, Wolfgang; Berweck, Steffen; Staudt, Martin; Berndt, Markus; Kluger, G. (Neuropediatrics, 2021)
Background Childhood stroke is rare and can predispose to post-stroke epilepsy. The purpose of this study was to evaluate long-term quality of life (QoL) in patients with childhood stroke, focusing on epileptic aspects.Method This involves a retrospective study of 98 patients with childhood stroke (pre- and neonatal strokes excluded), who had been inpatients between 1986 and 2003 for early rehabilitation. Data were obtained via interviews using a standardized questionnaire: QoL evaluation with KINDL, functional outcome with Barthel Index, and motor handicaps-assessment with modified Rankin Score.Results Forty-nine of 98 patients (31 males, mean follow-up 16 years, range 8–25 years) were included. Six patients passed away (three of sudden unexpected death in epilepsy). At least one epileptic seizure occurred in 27/49 patients (occurrence: 2 days–13 years.; mean 3.3 years.). Epilepsy manifested in 19/49 patients. No correlation was found between the development of epilepsy and the location or etiology of the stroke. The presence of functional independence was significantly higher in seizure-free patients and in patients without epilepsy. For the external assessment (filled in for the patient by the parent/caregiver), there was no significant difference in QoL in patients with and without epilepsy; however, in the in-person KINDL questionnaire a significantly lower QoL was noted in epilepsy patients compared with patients without epilepsy.Conclusion One important finding in our study is that in the long-term course 39% of patients developed epilepsy after a childhood stroke. It occurred as late as 13 years after the acute episode and affected the QoL especially in cognitively less handicapped patients.
Keywords: childhood stroke; risk of epilepsy; quality of life; long-term outcome